Can we make participatory NTFP monitoring work?: lessons learnt from the development of a multi-stakeholder system in Northern Laos - Boissiere, M.; Bastide, F; Basuki, I; Pfund, J.L; Boucard, A. (Springer, 2014)
Monitoring natural resources is essential for their successful and sustainable management. Community participation should enable local people to take ownership of the monitoring and ensure that it is cost-effective. But even then, success is often elusive. We developed a participatory Non Timber Forest Product (NTFP) monitoring system in 6 upland villages of Luang Prabang Province, Lao PDR, using focus group discussions, interviews, village meetings and direct observations. We used simple approaches to select resources, discuss issues, and develop a cost-effective NTFP monitoring system. Communities usually relied on shifting cultivation, fishing and collection of NTFPs. Gold mining activities affected livelihoods in three villages, which had better access to markets. Participatory monitoring looks less successful when external economic pressures or a major environmental threat disturbs local livelihoods. In the case of gold mining, we observed the prioritization of villagers' activities towards this sudden new economic opportunity. In contrast, communities not impacted by mining participated more actively in data collection. They understood how the data could be used to influence the local government, to achieve more beneficial land management for all stakeholders concerned. We believe that participatory NTFP monitoring can work and is an important tool for decision-making and economic empowerment for local communities. We identified the conditions under which participatory NTFP monitoring could work: reaching a shared understanding of what needs to be monitored and how; testing and refining a simple monitoring system; and integrating local government concerns with those of other stakeholders.